EBIC study of Au / n-type GaN Schottky contacts - Moldovan, Grigore; Harrison, Ian; Brown, Paul D. (IOP Publishing Ltd, 2003)
The performance of Au / n-type GaN Schottky contacts is strongly dependent on the GaN surface processing prior to contacting. Current-voltage and EBIC line scans demonstrate that KOH treatment acts to degrade the Schottky contacts. EBIC imaging reveals the differing sub-grain boundary structures of MBE and MOCVD grown GaN / sapphire. The KOH treatment acts to uniformly change the properties of the GaN surface, rather than having a localised effect.